Investigation Of Wire Sweep During Pbga Encapsulation Process Using Fluid Structure Interaction - Ramdan, Dadan (2013)

(untitled)
The reduction of IC chip size has a significant impact to the modern electronic industry especially on the circuit design and IC assembly process. The increasing of I/O counts in a small scale IC chip result in severe wire deformation and deformation issues during transfer moulding process. In this research, visualization of wire sweep phenomenon during the encapsulation process of plastic ball grid array (PBGA) package is studied through a three-dimensional (3D) fluid structure interaction (FSI) technique; which FV- and FE-based software are connected by using mesh-based parallel code coupling interface (MpCCI). The effect of polymer rheology, inlet pressure, arrangement of inlet gate, number of stacked die, wire diameter and size of mould cavity vents, on the melt flow behaviour, wire sweep, filling time, cavity pressure and stress distributions, are mainly studied. A 3D model of mould and wires was created by using GAMBIT, and the fluid/structure interaction was simulated by using FLUENT and ABAQUS software integrated with MpCCI for the real-time calculations. The Castro-Macosko model and Kamal model are used to incorporate the polymer rheology and the Volume of Fluid (VOF) technique is applied for melt front tracking. User-defined functions (UDFs) were incorporated to allow the curing kinetics. However, in the experimental work, the effects of FSI phenomenon in the PBGA package was studied using a scaled-up package size to mimic the encapsulation process. The effects of stacked die, inlet gate arrangement, outlet vent, and inlet pressure of mould cavity on the melt flow behaviour and wire sweep were xxxiii investigated. The constant viscosity of test fluid was utilised for experiment. The numerical results of melt front patterns and wire sweep were compared with the experimental results and it was found in good conformity. Three types of Epoxy Moulding Compound (EMC) were utilized for the study of fluid flow within the mould cavity. The melt front profiles and viscosity versus shear rate for all cases were analysed and presented. The numerical results of melt front behaviour and wire sweep were compared with the previous experimental results and found in good agreement. In the present study, the lower viscosity shows the lower air trap, lower pressure distributions and lower wire deformation. Optimised design of the PBGA gives better PBGA encapsulation process and minimises the wire sweep. The physical and process parameter (i.e., pressure inlet, wire diameter, vent height) were optimised via response surface methodology (RSM) using central composite design (CCD) to minimise the deformation of wire sweep, filling time and void in package during the PBGA encapsulation process. Fluid structure interaction (FSI) was considered in the optimisation of the PBGA encapsulation process. The optimum empirical models were tested and well confirmed with the simulation results. The optimum design of the PBGA with 12 wires for both physical and process parameters ware characterised by 5.57 MPa inlet pressure, 0.05 mm wire diameter, and 0.36 mm vent height. Therefore, the strength of MpCCI code coupling in handling FSI problems is proven to be excellent. This present work is expected to be a reference and guideline for microelectronics industry.